Cardiovascular disease and risk of lung cancer incidence and mortality: A nationwide matched cohort study - Wang, Ce; Lu, Donghao; Cronin-Fenton, Deirdre; Huang, Chen; Liew, Zeyan; Wei, Dang; Qin, Guoyou; Yu, Yongfu; Li, Jiong (Frontiers in Oncology, 2022)
Purpose Previous studies have suggested a link between cardiovascular disease (CVD) and the subsequent development of lung cancer. However, empirical evidence on the association of CVDs, particularly type-specific CVDs, with lung cancer incidence and survival remains limited. Methods The cohort study included 306,285 patients with CVD and 1,222,140 individuals without CVD. We performed stratified Cox regression to estimate the hazard ratio (HR). Results During up to 42 years of follow-up, 243 (0.08%) and 537 (0.04%) participants were diagnosed with lung cancer among CVD patients and matched individuals, respectively. Patients with CVD had a 67% increased risk of lung cancer (HR: 1.67, 95% confidence interval [CI]: 1.42–1.96). The increased risks were observed in patients with heart disease (1.93, 1.30–2.85), vascular disease (1.88, 1.35–2.61), and hypertensive disease (1.46, 1.15–1.85), respectively. Patients with CVD had a 95% increased risk of lung cancer mortality (1.95, 1.50–2.55), particularly vascular disease (3.24, 1.74–6.02) and heart disease (2.29, 1.23–4.26). Patients with CVD diagnosed in middle adulthood (>40 years old) tended to have a higher incidence risk (3.44, 2.28–5.19) and mortality (3.67, 1.80–7.46) than those diagnosed at younger ages. Conclusions Our findings on the association of CVD diagnosis, especially heart and vascular disease, with increased risk of lung cancer incidence and mortality suggest that CVD contributes to the development and worsening of lung cancer survival. In particular, people with CVD diagnosed in middle adulthood (>40 years old) would benefit from early preventive evaluation and screening for lung cancer.